An improved robot calibration method using the modified adjoint error model based on POE. (1st October 2020) - Jiang, Zizhen; Gao, Wenbin; Yu, Xiaoliu
Abstract : The robot calibration exists many excellent performances by using the POE formula, but it demands extra works to deal with the problems of the joint twist constrains. Thus, the Adjoint error model is proposed to solve these problems, which can be developed further. In this paper, we have modified the Adjoint error model and improved the calibration method. On the one hand, we conduct the formula entirely for the serial robot based on the modified Adjoint error model, so as to give an explicit and unified calibration model. On the other, the method of updating kinematic parameters is also simplified, comparing the previous calibration methods with the Adjoint error model, which can improve the convergence rate and optimize our calibration process. For verifying this method, the simulations on the typical robots of PUMA 560 and SCARA are presented, and the results show that this method has evident superiorities. GRAPHICAL ABSTRACT: UF0001